(untitled) (Third Sector Social Economic Review, 2024)
Digitalization and artificial intelligence are becoming increasingly important in today’s business world. In sectors like insurance, which heavily focus on risk management and financial services, the potential of these technologies is significant. Digitalization is the process through which businesses transform their operations using digital technologies, while artificial intelligence enables computers to exhibit human-like intelligence and learning capabilities. To effectively leverage these technologies, businesses need to enhance their employees’ knowledge and skills regarding artificial intelligence and digitalization. This research was conducted on 380 employees working in the insurance sector across Turkey. Data were collected using a survey method, and analyses were carried out using t-tests, ANOVA, structural equation modeling, and correlation analysis. The findings of the research examined the impact of demographic characteristics such as gender, marital status, education level, age, and experience in the sector on employees’ perceptions of artificial intelligence, as well as the effect of these perceptions on employee performance. The results indicate that digitalization and artificial intelligence applications have a significant impact on employee performance in the insurance sector. These findings underscore the necessity for insurance companies to develop their employees’ knowledge and skills as part of their digital transformation processes. The research contributes significantly to the increasing adoption of digitalization and artificial intelligence applications in the insurance sector and helps employees adapt to these technologies.